Carbon Costs of Indonesian Forested Land Conversion to Oil Palm Plantations - Sri Walyoto (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
This article analyzes the loss of carbon dioxide (CO2) released in the forest conversion to oil palm plantations. This research data gathered from the relevant secondary data and relate published reports. This research finds that a loss of release of carbon dioxide (CO2) per hectare of US 9,800 with a carbon price of USD2 of US 14,000 carbon price of USD3 and US 19,600 in carbon price of USD4. In addition, this conversion also has a significant impact on global warming (GWP) and global climate change.Â Keywords: oil palm plantation, CO2 release, GWP, climate change.Â